Blood-Derived Plasma Protein Biomarkers for Alzheimer’s Disease in Han Chinese - Cheng, Zaohuo; Yin, Jiajun; Yuan, Hongwei; Jin, Chunhui; Zhang, Fuquan; Wang, Zhiqiang; Liu, Xiaowei; Wu, Yue; Wang, Tao; Xiao, Shifu (Frontiers in Aging Neuroscience, 2018)
It is well known that Alzheimer’s disease (AD) is one of the most common progressive neurodegenerative diseases; it begins gradually, and therefore, no effective medicine is administered in the beginning. Thus, the early diagnosis and prevention of AD is crucial. The present study focused on comparing the plasma protein changes between patients with AD and their healthy counterparts, aiming to explore a specific protein panel as a potential biomarker for AD patients in Han Chinese. Hence, we recruited and collected plasma samples from 98 AD patients and 101 elderly healthy controls from Wuxi and Shanghai Mental Health Centers. Using Luminex assay, we investigated the expression levels of fifty plasma proteins in these samples. Thirty-two out of fifty proteins were found to be significantly different between AD patients and healthy controls (P < 0.05). Furthermore, an eight-protein panel that included brain-derived neurotrophic factor (BDNF), angiotensinogen (AGT), insulin-like growth factor binding protein 2 (IGFBP-2), osteopontin (OPN), cathepsin D, serum amyloid P component (SAP), complement C4, and prealbumin (transthyretin, TTR) showed the highest determinative score for AD and healthy controls (all P = 0.00). In conclusion, these findings suggest that a combination of eight plasma proteins can serve as a promising diagnostic biomarker for AD with high sensitivity and specificity in Han Chinese populations; the eight plasma proteins were proven important for AD diagnosis by further cross-validation studies within the AD cohort.